Feeding Activity of Heliotis armigera Hubner Larvae on Food Formulated with Ethanol Extracts of Bitter Melon Leaves (Momordica charantia L.), Galangal Leaves (Lactuna indica L.) and Adjuvant Agrestic - Nursal; Arlen Hanel Jhon (International Journal of Ecophysiology, 2024)
The research on the Feeding Activity of Heliotis armigera Hubner larvae on food formulated with ethanol extracts of bitter melon leaves (Momordica charantia L.), galangal leaves (Lactuna indica L.) and adjuvant agrestic has been conducted. This study used the ratio formulation of bitter melon and galangal (1:1, 1:2, 2:1), 1% adtjuvan agristik. The feeding activity was observed using the feeding method with several concentrations (0.00, 0.58, 1.16, 1.74, 2.32, 2.92) and 15 larvae for iterations using a completely randomized design (CRD). The data from the observations were analyzed using variance; if there were differences, it would proceed to the Duncan test of 5%. Insect feeding activity is influenced by food containing concentrations of 1.16% - 2.92% of a formulation (1:1, 1:2, 2:1) of bitter melon leaf extract, galangal leaf extract, and 1% agrestic adjuvant, leading to a decrease in insect growth rate (RGR). The insect’s feeding ability (RCR), ability to convert consumed food into usable nutrients (ECI), and ability to digest food and utilize it (ECD) are also reduced. Conversely, the ability to digest insect food (AD) is increased. The best formulation and concentration are (2:1) and (1.74%).